Sorafenib in Advanced Hepatocellular Carcinoma: A Nationwide Retrospective Study of Efficacy and Tolerability - Anne Helene Køstner; Morten Sorensen; René Krøjgaard Olesen; Henning Grønbæk; Ulrik Lassen; Morten Ladekarl (The Scientific World Journal)
Background. Advanced HCC is a clinical challenge with limited treatment options. The multikinase inhibitor sorafenib is the first and only agent showing a survival benefit in these patients. In this study we evaluate the efficacy and tolerability of sorafenib in an unselected patient population. Furthermore we explore the role of alpha-fetoprotein (αFP) as a potential biomarker for treatment efficacy and correlation to survival. Methods. Seventy-six patients with advanced HCC, not eligible for locoregional therapy, treated with sorafenib between 2007 and 2009 were included. Followup was until 2011. Results. Patients in PS 0-1 had a median overall survival (mOS) of 6.2 months, compared to 1.8 months in patients with poorer PS (P=0.005). Child-Pugh A patients had a mOS of 6.6 months versus 3.6 months among patients in Child-Pugh B or C (P=0.0001). Serum αFP ≥ 200 at baseline was prognostic for a shorter survival. All patients with radiologically verified tumor response and baseline αFP ≥ 200 experienced a significant decline in αFP within the first four weeks of treatment. Conclusion. The survival of patients with advanced HCC treated with sorafenib is dependent on performance status and liver function. Treatment of patients with compromised liver function and poor performance status cannot be recommended. The correlation between αFP and objective tumor response warrants further investigation.